Structural basis of transcription inhibition by the DNA mimic protein Ocr of bacteriophage T7. - Ye,F; Kotta-Loizou,I; Jovanovic,M; Liu,X; Dryden,DT; Buck,M; Zhang,X (eLife, 2020)
Bacteriophage T7 infects Escherichia coli and evades the host restriction/modification system. The Ocr protein of T7 was shown to exist as a dimer mimicking DNA and to bind to host restriction enzymes, thus preventing the degradation of the viral genome by the host. Here we report that Ocr can also inhibit host transcription by directly binding to bacterial RNA polymerase (RNAP) and competing with the recruitment of RNAP by sigma factors. Using cryo electron microscopy, we determined the structures of Ocr bound to RNAP. The structures show that an Ocr dimer binds to RNAP in the cleft, where key regions of sigma bind and where DNA resides during transcription synthesis, thus providing a structural basis for the transcription inhibition. Our results reveal the versatility of Ocr in interfering with host systems and suggest possible strategies that could be exploited in adopting DNA mimicry as a basis for forming novel antibiotics.